Insecure attachment is associated with math anxiety in middle childhood - Bosmans, Guy; De Smedt, Bert (Frontiers in Psychology, 2015)
Children’s anxiety for situations requiring mathematical problem solving, a concept referred to as math anxiety, has a unique and detrimental impact on concurrent and long-term mathematics achievement and life success. Little is known about the factors that contribute to the emergence of math anxiety. The current study builds on the hypothesis that math anxiety might reflect a maladaptive affect-regulation mechanism that is characteristic for insecure attachment relationships. To test this hypothesis, 87 children primary school children (Mage = 10.34 years; SDage = 0.63) filled out questionnaires measuring insecure attachment and math anxiety. They all completed a timed and untimed standardized test of mathematics achievement. Our data revealed that individual differences in math anxiety were significantly related to insecure attachment, independent of age, sex and IQ. Both tests of mathematics achievement were associated with insecure attachment and this effect was mediated by math anxiety. This study is the first to indicate that math anxiety might develop in the context of insecure parent-child attachment relationships.